Kelayakan Bisnis Mesin Combine Harvester Rice di Kelompok Tani Sido Mukti di Desa Luwung - Putri Valentina Wardiarsana; Prihono Prihono (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The agricultural sector in Indonesia faces challenges such as labor shortages, increasing harvesting costs, and the need for improved efficiency, making the use of modern harvesting technology like Combine Harvester Rice machines increasingly important. This study aims to analyze the business feasibility of Combine Harvester Rice machines in the Sido Mukti Farmer Group in Luwung Village based on Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). The research employed a descriptive quantitative method with a case study approach, and data were collected through observation, interviews, questionnaires, and documentation involving 43 respondents. The analyzed data include initial investment costs of Rp545,000,000 for the Bimo 110 Plus and Rp499,000,000 for the Bimo 102 SS, operational costs of approximately Rp1,742,000 per hectare, rental rates of approximately Rp2,450,000 per hectare, maintenance costs of approximately Rp7,500,000 per year, an interest rate of 10%–12%, and an economic life of 8 years. The results show that the Bimo 110 Plus machine is not financially feasible, with an NPV of Rp -11,507,380, PP of 5.45 years, PI of 0.98, and IRR of 9.6%. In contrast, the Bimo 102 SS machine is financially feasible, with an NPV of Rp34,492,620, PP of 5 years, PI of 1.07, and IRR of 12%. Therefore, the Bimo 102 SS is more recommended for use as it provides better economic value for the farmer group.